A simulation study to evaluate the performance of FMS using routing flexibility. (3rd November 2022) - Mashhood, Huzefa; Ali, Mohammed
Flexible manufacturing systems (FMS) are used to promote technological advancement in modern industries. Most studies have highlighted the difficulties in modelling FMS for analyses. The aim of this study is to develop a demonstrative model of FMS using ARENA and to study effects of routing flexibility (RF) on its performance. Conceptual simulation models have been developed for various RF levels. Simulation results are used to find the optimum RF level. To validate the simulation results, grey relational analysis (GRA) and technique for order preference by similarity to ideal solution (TOPSIS) have been used. The study has shown that combination of RF1 level and inter-arrival time of 15 minutes results in optimised performance for the FMS. There are also the effects of dispatching rules on the performance of FMS. It is observed that both the rules help in increasing the average system utilisation and the system output.